Prevalence of respiratory disease and associated factors in an urban area of Delhi - Chhabra Pragti; Sharma Geetanjali; Kannan Anjur (Wolters Kluwer Medknow Publications, 2008)
Objectives: To study the prevalence of respiratory morbidity and its associated factors in urban Delhi. Study Design and Setting: A cross-sectional, house-to-house survey was conducted in an urban upper middle class locality. Materials and Methods: All the residents aged 18 years or more were administered a questionnaire to identify the major symptoms of chronic respiratory tract disease - chronic cough, chronic phlegm, dyspnea and wheezing. The prevalence of all these symptoms in different groups was calculated. Chi square test and logistic regression were applied to determine the significant factors. Results: A total of 3465 individuals were interviewed of which 1756 (50.68%) were males and 1709 (49.3%) were females. Only 9.05% of the men smoked. The overall prevalence of chronic cough, chronic phlegm and dyspnea was 2.0%, 1.2% and 3.4%, respectively. The prevalence of wheezing was 3.2%. All the symptoms increased with age ( P < 0.05). No significant difference was observed in these symptoms between males and females. Less educated and retired individuals were more likely to have respiratory symptoms. The prevalence of chronic cough, chronic phlegm, dyspnea and wheezing was 5.8%, 2.9%, 9.9% and 8.7%, respectively, among smokers, which was significantly higher than that observed in nonsmokers. Logistic regression analysis revealed that age and smoking remained significant factors for occurrence of all the respiratory symptoms.